# Yahoo Web Search

1. Sort by

1. ### If y=K/X n is a power to X, the independant value is??? A. y B. k C. X D. N?

ans : [ X ] ------

1 Answers · Science & Mathematics · 24/05/2010

2. ### how would I prove that an equation involving combinations are equal?

k*C(n+1,k) = k * (n+1)!/(k!(n+1-k)!) = (n+1)!/((k-1)!(n+1-k)!) = (n+1) * n!/((k-1)!(n+1-k)!) = (n+1) * C(n, k-1)

1 Answers · Science & Mathematics · 14/08/2007

3. ### Can you help me find the first and second derivative?

Use the Quotient Rule. = [1-e^(-alpha(u)] [k+(c)(lamba)] - [k+(c)(lamda)(u)) (-e^(-alpha(u)) (-alpha)] / (1-e^(-alpha)(u)]^2 Note...

1 Answers · Science & Mathematics · 27/03/2008

4. ### Prove using a combinatorial arguments?

n * C(n-1, k-1) = n * [(n-1)! / ((k-1)! (n-k)!)] = n! / ((k-1)! (n-k)!) = k * [n! / (k! (n-k)!)] = k * C(n, k). I hope this helps!

1 Answers · Science & Mathematics · 20/11/2011

5. ### Solve the recursive relation by finding a closed-form formula and vice versa?

Note that c_k - c_{k-1} = 2k. The sum of (c_k - c_{k-1}) from k=1 to n is (c_n - c...

3 Answers · Science & Mathematics · 21/03/2008

6. ### algebra Math problems help?

4x + 7 - 9x = 9 4x - 9x = 9 - 7 -5x = 2 x = -2/5 = -0.4

1 Answers · Science & Mathematics · 16/04/2011

7. ### Matrix question?

... A and B are in K(C) Xt (A+B) X = (... C X^N will be in K(C) by induction. But you can realise...

2 Answers · Science & Mathematics · 22/10/2007

8. ### i really need help with math problems please?

1) if log k= c log v + log p, what is the value of k? start with the RHS: two ...

2 Answers · Science & Mathematics · 31/03/2008

9. ### derivative help please :) 10 points for the best answer!!?

ƒ(k) = √[k + (kc)^2], assuming c is a constant, and k is the only variable. ƒ...v, by chain rule, we get: ƒ'(k) = u' ⋅ v ⋅ u^(v - 1) ƒ'(k) = [1 + 2(kc)] ⋅ 1/2 ⋅ [k + (kc)^2]^(-1/2) ƒ'(k) = (1 + 2k − 2c) / (2√[k + (kc...

3 Answers · Science & Mathematics · 23/02/2013

10. ### How to prove this combinatoric identity?

Pascal's rule: C(n,k) = C(n-1,k) + C(n-1, k-1) First, show...m!n!) out the window to get sum [k=0 to n] (-1)^k * C(n, k) = 0 which again can be shown easily by...

2 Answers · Science & Mathematics · 30/07/2009